2011
DOI: 10.1007/s00203-011-0770-1
|View full text |Cite
|
Sign up to set email alerts
|

Lectin genes in the Frankia alni genome

Abstract: Frankia alni strain ACN14a's genome was scanned for the presence of determinants involved in interactions with its host plant, Alnus spp. One such determinant type is lectin, proteins that bind specifically to sugar motifs. The genome of F. alni was found to contain 7 such lectin-coding genes, five of which were of the ricinB-type. The proteins coded by these genes contain either only the lectin domain, or also a heat shock protein or a serine-threonine kinase domain upstream. These lectins were found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…638 [47] , Azoarcus BH72 [39] or the symbiotic actinobacterium Frankia sp . [48] have only a reduced set of cell-wall degrading enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…638 [47] , Azoarcus BH72 [39] or the symbiotic actinobacterium Frankia sp . [48] have only a reduced set of cell-wall degrading enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Lectins can be produced by the host or by the microorganisms to facilitate binding to the host (Lis and Sharon, ). Interestingly, recent investigations revealed that the genome of F. alni ACN14a contains five genes with a ricin B lectin domain (Pujic et al ., ), and a possible role for the lectins in Frankia was suggested to be to permit binding of microbial cells to root hairs to help symbiosis to occur under conditions of low Frankia cell numbers such as those in pioneer situations.…”
Section: The Infection Processmentioning
confidence: 99%
“…The structural and biochemical properties of distinct fungal lectins have been explored recently . The various physiological roles proposed for fungal lectins include identification of host during ectomycorrhizal symbiosis (Pujic et al 2012), facilitating association with algae and cyanobacteria in lichens (Diaz et al 2011;Singh & Walia, 2014) and yeast flocculation (Singh et al 2011).…”
Section: Introductionmentioning
confidence: 99%